2015
DOI: 10.1021/acs.jmedchem.5b00915
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Biological Evaluation of Costunolide, Parthenolide, and Their Fluorinated Analogues

Abstract: Inspired by the biosynthesis of sesquiterpene lactones (SLs), herein we report the asymmetric total synthesis of the germacrane ring (24). The synthetic strategy features a selective aldol reaction between β,γ-unsaturated chiral sulfonylamide 15a and aldehyde 13, as well as the intramolecular α-alkylation of sulfone 21 to construct a 10-membered carbocylic ring. The key intermediate 24 can be used to prepare the natural products costunolide and parthenolide (PTL), which are the key precursors for transformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…To further characterize the physical properties of the nanovector formulation we conducted experiments to determine particle stability, PTL release profile and copolymer stability in PBS and human serum (HS). Standard dosimetry in vivo requires multiple doses of PTL due to its short half‐life (in the order of hours), which means that particle stability should be evaluated over hours and days. Consistent correlation DLS data of unfiltered samples showed that particles were stable over the course of 6 d in PBS at 37 °C (Figure S7, Supporting Information), which was supported by AF4 (Figure S8, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…To further characterize the physical properties of the nanovector formulation we conducted experiments to determine particle stability, PTL release profile and copolymer stability in PBS and human serum (HS). Standard dosimetry in vivo requires multiple doses of PTL due to its short half‐life (in the order of hours), which means that particle stability should be evaluated over hours and days. Consistent correlation DLS data of unfiltered samples showed that particles were stable over the course of 6 d in PBS at 37 °C (Figure S7, Supporting Information), which was supported by AF4 (Figure S8, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Germacranolides are key precursors of other sesquiterpene lactones with various polycyclic skeletons, such as guaianolides, eudesmanolides, etc. [4]. Costunolide, a colorless crystalline powder with a molecular formula of C 15 H 20 O 2 and a molecular weight of 232.318 g/mol, is a well-known sesquiterpene lactone in the germacranolides series.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of effort has been made to overcome its instability in both acidic and basic conditions and improve its solubility and bioavailability [191][192][193][194][195][196][197][198][199]. Several new water-soluble PN derivatives have been designed, synthesized and their activity has been evaluated in vitro and in vivo [43,47,[193][194][195][196][197][198][199][200][201][202]. Better solubility and higher anticancer activity have been recently obtained with PN derivatives prepared through the aza-Michael addition of nitrogen-containing anticancer drugs such as cytarabine and melphalan [200].…”
Section: Discussionmentioning
confidence: 99%